2005
DOI: 10.5511/plantbiotechnology.22.371
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors for sugar-inducible genes

Abstract: Expression of a variety of sink-related genes for the synthesis of storage compounds are up-regulated in response to increased levels of sugars, while expression of many genes involved in photosynthesis and the breakdown of storage compounds is repressed by sugars. Despite of extensive studies on sugar signaling in plants, only few transcription factors involved in the expression of sugar-inducible genes have been identified so far. A transgenic Arabidopsis thaliana line carrying luciferase gene under the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Table S1 ). The positive clones included three plant-specific B3 domain proteins such as FUS3 and LEC2 and five homeobox-containing ATHB proteins, both of which have been shown to act on the sugar-responsible minimal promoters through binding to the different cis -element from the CMSRE-1 (Morikami et al 2005b ). Among the rest, we identified two clones, corresponding to At5g21960 and At1g19210, which we designated as A ctivator protein binding to C MS RE -1 1 and 2 (ACRE1 and ACRE2), respectively, after we confirmed that they bound to CMSRE-1 (described below).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table S1 ). The positive clones included three plant-specific B3 domain proteins such as FUS3 and LEC2 and five homeobox-containing ATHB proteins, both of which have been shown to act on the sugar-responsible minimal promoters through binding to the different cis -element from the CMSRE-1 (Morikami et al 2005b ). Among the rest, we identified two clones, corresponding to At5g21960 and At1g19210, which we designated as A ctivator protein binding to C MS RE -1 1 and 2 (ACRE1 and ACRE2), respectively, after we confirmed that they bound to CMSRE-1 (described below).…”
Section: Resultsmentioning
confidence: 99%
“…The CMSRE-1 sequence has been shown to be essential for sugar-inducible expression from Spo min and BAD promoters in tobacco and Arabidopsis (Maeo et al 2001 ; Morikami et al 2005a , b ). In sweet potato, it was reported that the Spo min promoter-GUS gene was upregulated by exogenously supplied sucrose in leaves and stems and expressed highly and constitutively in storage roots (Honma and Yamakawa 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations